KORUPSI PENGADAAN PESAWAT TERBANG DI KABUPATEN JAYAWIJAYA - Atek, Liboria G; Ndoen, Marthen L (Universitas Kristen Satya Wacana, 2020)
This article describes the corruption case of aircraft procurement in Jayawijaya Regency, Papua, in the 2002 and 2003 Fiscal Year, under the leadership of Regent Jayawijaya, David A. Hubi. This article is the result of field research using a qualitative method with an analytical descriptive approach. The results of this study indicate that, the direct involvement of Regent Jayawijaya with a view to enriching oneself or others is, in fact, not too great. Corruption is mostly done by subordinates and entrepreneurs who become partners. However, as a leader, like it or not, and ready or not, David A. Hubi still has to take responsibility. David A. Hubi was found guilty by the Court on charges: (1) unable to control budget use properly which results in markups; and (2) abuse power to issue to policy of his own volition.